Pengaruh Dimensi Keadilan, Sosialisasi Pajak, Sanksi Pajak, Penghasilan Wajib Pajak dan Pemeriksaan Pajak Terhadap Kepatuhan WPOP UMKM - Nadiani Putri Utama, Putu; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p28, 2019)
This study aims to determine the effect of the dimensions of justice, socialization of taxes, tax sanctions, income taxpayers, and tax audits of individual taxpayer compliance Micro, Small and Medium Enterprises (MSMEs) registered at the Pratama Tax Service Office (KPP) Gianyar in 2017. The theories used in this study are Attribution Theory and Theory of Planned Behavior. A total of 100 MSME Personal Taxpayers registered at KPP Pratama Gianyar were selected as respondents using the Slovin formula. The research method used was accidental sampling using media questionnaires and technical analysis of the data of this study using classical assumption test analysis and multiple linear regression. The results of this study indicate that the dimensions of justice, tax socialization, tax sanctions, income of taxpayers, and tax audits have a positive and significant effect on taxpayer compliance with individual SMEs. Keywords: UMKM taxpayer compliance, dimensions of justice, socialization, sanctions, income, tax audit.